2021
DOI: 10.1016/j.cub.2020.11.073
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Ca2+ Signaling Pathway Coordinates Environmental Phosphorus Sensing and Nitrogen Metabolism in Marine Diatoms

Abstract: Highlights d Phosphorus (P)-limited diatoms sense P via a Ca 2+dependent signaling pathway d P-Ca 2+ signaling is employed by representative centric and pennate diatom species d Rapid cross-talk with N metabolism mediates diatom recovery responses to P resupply d P-Ca 2+ signaling coordinates diatom recovery responses from P limitation

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 77 publications
2
32
0
Order By: Relevance
“…As discussed in this section, an aequorin-based Ca 2+ sensor has already been used in P. tricornutum ; however, the development of transgenic lines, also stably expressing other novel GECIs in different subcellular compartments, could represent a useful tool to address the above-mentioned question in diatoms too. Examples relating to this are two recently published works in which the expression of the previously mentioned R-GECO1 in P. tricornutum and Thalassiosira pseudonana has allowed both the identification of a novel class of Na + - and Ca 2+ -permeable, voltage-gated channels, and the discovery of a Ca 2+ signalling pathway in diatoms to sense and rapidly respond to increases in phosphorus availability ( Helliwell et al , 2019 , 2021 ).…”
Section: Molecular Tools To Monitor and Measure In Vivo Intracellular Ca 2+ Concentrations In Micromentioning
confidence: 92%
“…As discussed in this section, an aequorin-based Ca 2+ sensor has already been used in P. tricornutum ; however, the development of transgenic lines, also stably expressing other novel GECIs in different subcellular compartments, could represent a useful tool to address the above-mentioned question in diatoms too. Examples relating to this are two recently published works in which the expression of the previously mentioned R-GECO1 in P. tricornutum and Thalassiosira pseudonana has allowed both the identification of a novel class of Na + - and Ca 2+ -permeable, voltage-gated channels, and the discovery of a Ca 2+ signalling pathway in diatoms to sense and rapidly respond to increases in phosphorus availability ( Helliwell et al , 2019 , 2021 ).…”
Section: Molecular Tools To Monitor and Measure In Vivo Intracellular Ca 2+ Concentrations In Micromentioning
confidence: 92%
“…However, growth is a rather late-stage indicator of recovery, representing the integrated end product of the physiological and biochemical pathways that allow cells to capitalize when limiting resources become available. In this issue of Current Biology, a study by Helliwell et al 14 explores the molecular underpinnings of this rapid recovery response to P limitation in diatoms, documenting the existence of a novel Ca 2+ -based signaling pathway not previously described in eukaryotes that mediates the response to P resupply.…”
mentioning
confidence: 98%
“…In the new study, Helliwell et al 14 provide the first glimpse into the earliest molecular response of diatoms to recovery from P limitation, even before growth resumption. Using the welldescribed model diatom Phaeodactylum tricornutum transformed to express R-GECO1, a fluorescence-based sensor of intracellular Ca 2+ , the authors observed an increase in Ca 2+ within seconds following resupply of P to P-limited cultures (Figure 1).…”
mentioning
confidence: 99%
See 2 more Smart Citations